2022
DOI: 10.3390/app12157698
|View full text |Cite
|
Sign up to set email alerts
|

Martens Hardness of CAD/CAM Resin-Based Composites

Abstract: (1) Background: The properties of CAD/CAM resin-based composites differ due to differences in their composition. Instrumented indentation testing can help to analyze these differences with respect to hardness, as well as energy-converting capabilities due to viscoelastic behavior. (2) Methods: Eleven materials were investigated using instrumented indentation testing. Indentation depth (hr), Martens hardness (HM), indentation hardness (HIT), indentation modulus (EIT), the elastic part of indentation work (ηIT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The null hypothesis tested in this study was rejected because there were several significant differences between the evaluated parameters of the tested CAD/CAM materials both initially and after aging. Indeed, the highest FS values was observed in Grandio (324.7 MPa), followed by Shofu (164.3 MPa) and Vita (161.1 MPa), and the FS values were in accordance with those provided by the manufacturers (Grandio 330 MPa, Shofu 170-190 MPa, Vita 150-160 MPa) [7,15,36]. Shofu exhibited significantly greater FS values than Vita, but these results are in contrast to the results reported in a previous study [34], where Shofu showed comparable FS values to Vita.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The null hypothesis tested in this study was rejected because there were several significant differences between the evaluated parameters of the tested CAD/CAM materials both initially and after aging. Indeed, the highest FS values was observed in Grandio (324.7 MPa), followed by Shofu (164.3 MPa) and Vita (161.1 MPa), and the FS values were in accordance with those provided by the manufacturers (Grandio 330 MPa, Shofu 170-190 MPa, Vita 150-160 MPa) [7,15,36]. Shofu exhibited significantly greater FS values than Vita, but these results are in contrast to the results reported in a previous study [34], where Shofu showed comparable FS values to Vita.…”
Section: Discussionsupporting
confidence: 73%
“…The hardness and modulus of elasticity of some CAD/CAM ceramics may resemble those of enamel (1.1-4.9 GPa and 50-120 GPa, respectively), while those of some CAD/CAM composites may be comparable to those of dentin (0.3-0.7 GPa and 10-40 GPa, respectively) [6]. Indeed, it has been reported that restorations of posterior teeth performed with CAD/CAM composites cause less abnormal tooth wear; they represent the main choice for the restoration of teeth in patients affected by bruxism [7,8]. Glassceramics, as well as glass-free-ceramics, exhibit values of the flexural modulus (Ef) and Vickers hardness that are considerably higher than those of resin composites (≥60 GPa, >4 GPa versus 9-20 GPa, 0.4 GPa, respectively) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since H IT shows a similar behavior and ranking as HM, a high proportion of plastic deformation is to be assumed for all materials. The elastic proportion is to be classified as low, especially for parts of the printed materials [ 40 ]. The highest stability under clinical bruxism loadings might be expected for CAM and astonishingly one printed system PL.…”
Section: Discussionmentioning
confidence: 99%
“…Only for two printed materials a higher value could be identified. Since the creep behavior C IT describes the further deformation of the material under constant force, the indentation depth for these materials increases under load [ 40 ]. Under clinical conditions with continuous load, such as bruxism, the deformations for these materials would therefore be higher.…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that the filler loading has more influential effect after 3 months storage than at dry condition except for PICN which showed lowest and significantly different nanonindentation creep after 24 h dry storage in agreement with similar studies [ 21 , 41 , 42 ]. The filler microstructure (volume percent, size and distribution) and resin matrix composition can influence the viscoelastic stability and mechanical properties of composite materials [ 43 , 44 ]; PICN (EN) showed the lowest nanoindentation creep at both storage conditions (24 h dry and 3 months water storage) and this can be attributed to the three dimensional skeleton provided by filler and resin matrix infiltration as compared to other CAD-CAM composite blocks [ 45 ], and it reflects the material stability under loads especially in cases of bruxism where ceramics might fail due to brittleness [ 46 ]. There was a significant negative correlation between both nanoindentation creep (µm) and nanohardness (GPa) at 24 h dry storage ( P = 0.009, R 2 = 0.77) and nanoindentation creep (µm) and elastic modulus (GPa) at 24 h dry storage (P = 0.006, R 2 = 0.80).…”
Section: Discussionmentioning
confidence: 99%